Operator calculus on the class of Sato’s hyperfunctions - Patra, M.I.; Sharyn, S.V. (Carpathian Mathematical Publications, 2013)
We construct a functional calculus for generators of analytic semigroups of operators on a Banach space. The symbol class of the calculus consists of hyperfunctions with a compact support in [0,∞). Domain of constructed calculus is dense in the Banach space.